Leading the way: Foreign direct investment and dairy value chain upgrading in Uganda - Van Campenhout, Bjorn; Minten, Bart; Swinnen, Johan (John Wiley & Sons, 2021)
Driven by increased demand from both local and export markets and facilitated by far-reaching liberalization and privatization policies, the dairy sub-sector in Uganda has undergone significant changes in the last decade. With a comparative advantage in milk production, the southwest of Uganda has started to attract considerable Foreign Direct Investment (FDI) in processing capacity, mainly targeting the export market. As a result, processing capacity increased five-fold and dairy became Uganda's third most important export product, coming from negligible amounts a decade earlier. In this study, we use data collected at different nodes within the value chain to identify some of the key innovations in these value chains. This is done by comparing the area that received the bulk of FDI to a similar area that did not. Furthermore, we also provide an econometric analysis that focuses on the integration of value chain actors into modern value chains more broadly defined. We find that dairy value chains are transforming rapidly, but innovations are more pronounced in areas that received the bulk of FDI. Our analysis further underscores the importance of milk collection centers, which often take the form of farmer cooperatives, in providing many of the support services that enable other actors in the value chain to produce sufficient milk, and maintain milk sanitation levels necessary for a modern export sector to emerg